2017
DOI: 10.1590/s1980-220x2016009903259
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sacred music on the spiritual well-being of bereaved relatives: a randomized clinical trial

Abstract: OBJECTIVE To evaluate the effects of instrumental sacred music and sacred music with vocals on the spiritual well-being of bereaved relatives. METHOD This is a randomized clinical trial carried out with family members bereaving the death of loved ones to cancer. Participants were allocated into three groups: Group 1 (control), Group 2 (experimental using sacred music with vocals) or Group 3 (experimental using instrumental sacred music). Spiritual well-being was assessed through the Spiritual Well-Being Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 14 publications
0
6
0
2
Order By: Relevance
“…Touch, hearing, breathing, circulation and reflexes are physically activated. [3][4][5][6][7] Thus, it is stated that some research has identified that the physiological effects of music involve sensory, hormonal and physio motor reactions, such as changes in metabolism, adrenaline release, respiratory rate regulation, changes in blood pressure, reduced fatigue, muscle tone and raising the threshold of sensory stimuli, improving attention and concentration. It is also known that it is an excellent therapeutic tool that is easy to use, affordable, has no side effects and can be used in various contexts and for various diseases.…”
Section: Music Is a Link And Ends Up Being A Link Because We At Nursimentioning
confidence: 99%
See 1 more Smart Citation
“…Touch, hearing, breathing, circulation and reflexes are physically activated. [3][4][5][6][7] Thus, it is stated that some research has identified that the physiological effects of music involve sensory, hormonal and physio motor reactions, such as changes in metabolism, adrenaline release, respiratory rate regulation, changes in blood pressure, reduced fatigue, muscle tone and raising the threshold of sensory stimuli, improving attention and concentration. It is also known that it is an excellent therapeutic tool that is easy to use, affordable, has no side effects and can be used in various contexts and for various diseases.…”
Section: Music Is a Link And Ends Up Being A Link Because We At Nursimentioning
confidence: 99%
“…2 In this perspective, in addition to music being a way for patients to cope with adversity, stressful and traumatic events, it also contributes to welcoming and communicating with health professionals, constituting bonds and commitments that should guide intervention projects. 3 It has also been pointed as a complementary therapeutic resource in the management and control of signs and symptoms, as well as in the field of communication, making care more humanized. 4 In this perspective, it is emphasized that the musical sensation begins in the child, as an emotion of pure auditory pleasure, evolving to the integrative regions of the brain, such as brain reflexes, evaluative conditioning, emotional contagion, visual imagination, episodic memory and musical expectation, thus composing amplifying schemes that enable the child to verbalize their stresses, anxieties, fears and frustrations.…”
mentioning
confidence: 99%
“…It is a transversal approach to a database of a randomized clinical study (7) , performed in the households of bereaved family members, who have lost their loved ones (parents or espouses) due to cancer. The data were gathered between January 2014 and March 2015, through a semi-structured form.…”
Section: Study Design Place and Periodmentioning
confidence: 99%
“…Post-loss music therapy, that is, when it is carried out after the patient's death, aims to provide bereaved family members social, emotional, and spiritual support in the process of elaborating the loss. Based on that supposition, an investigation has aimed to assess the effects of sacred music, instrumental and chanted ones, on the spiritual well-being of bereaved family members, despite not having statistically significant results, it identified that listening to sacred music tends to improve the levels of spiritual well-being for bereaved family members (7) , as well as it helps in the process of elaborating the loss.…”
Section: Introductionmentioning
confidence: 99%
“…fazê-lo permitir-se à reflexão sobre o seu adoecimento (BERGOLD;ALVIM, 2011)MARCON;SALES, 2014;VALENTIN et al, 2015),influenciam no estado de ânimo e humor, na fé e no suporte a dor da possibilidade de perda do ente querido(SANTOS; ZANINI;ESPERIDIÃO, 2015;SILVA et al, 2017;MARCON;SALES, 2014) A perspectiva da Musicoterapia direcionada a grupos e comunidades ou "musicoterapia social e comunitária" que vem romper, inclusive, com a musicoterapia tradicional, ultrapassando os limites físicos de um lugar, almeja a prática musical como mediadora da transformação social(ARNDT; CUNHA; VOLPI, 2016).…”
unclassified